Brood parasitism correlates with the strength of spatial autocorrelation of life history and defensive traits in Magpies. Issue 6 (1st June 2013) - Soler, Juan J.; Martín-Gálvez, David; de Neve, Liesbeth; Soler, Manuel
Abstract : Environmental characteristics of neighboring locations are generally more similar than those of distant locations. Selection pressures due to parasitism and other environmental conditions shape life history traits of hosts; thus, the probability of parasitism should be associated with the strength of spatial autocorrelation in life history and defensive traits of their hosts. Here we test this hypothesis in three different subpopulations of Magpie ( Pica pica ) parasitized by the Great Spotted Cuckoo ( Clamator glandarius ) during three breeding seasons. In some of the years and study plots, we found evidence of positive spatial autocorrelations for clutch size and parasitism rate, but not for laying date. As predicted, brood parasitism was associated with the strength of these spatial autocorrelations. Magpies that bred close to each other in areas of high risk of parasitism responded similarly to experimental parasitic eggs. Moreover, an elevated risk of parasitism eliminated the spatial autocorrelation for clutch size, which became randomly distributed. We discuss possible mechanisms explaining these associations, which may have important consequences for estimating evolutionary responses of hosts to parasitic infections and, therefore, for epidemiological, ecological, and evolutionary studies of host–parasite relationships.